Optimization of Sprinkling Parameters for Improved Irrigation Quality - Kozishkurt, Svitlana; Turcheniuk, Vasyl; Zhylchuk, Yuriy (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Under conditions of water scarcity and climate change, it is crucial to align irrigation intensity with the soil’s infiltration capacity. This study presents analytical modeling of the optimal sprinkling parameters (intensity and duration) taking into account the hydro-physical properties of soils, namely porosity and moisture content. Analytical equations were derived to determine the optimal irrigation duration that ensures efficient water use and prevents surface runoff formation. An example of calculations is provided for medium loamy soils under different sprinkling intensities.